(untitled) (HIMALAYA, 2025)
This editorial reflects on a period of institutional growth and editorial transition at HIMALAYA, the journal of the Association for Nepal and Himalayan Studies. Amid recent regional upheavals—including the May 2025 escalation between India and Pakistan—the journal reaffirms its commitment to rigorous, inclusive scholarship on the Himalayan region. Strategic developments such as the adoption of the Open Journal Systems (OJS) platform, a publishing partnership with the University of Edinburgh, and expanded print access through IngramSpark have significantly increased the journal’s global reach and accessibility. The editorial welcomes new team members who mark a generational and geographic expansion of HIMALAYA’s editorial vision. These include Associate Editor Dr. Shubham Sapkota (University of Colorado Boulder); Reviews Editor Dr. Zezhou Yang (Asia Research Institute, NUS); and in-region Assistant Editors Heidamteu Zeme (IIT Delhi), Gulal Salil (independent artist), and Yatin Batra (University of Delhi). Fatma Matar, a master’s student in visual anthropology at UiT The Arctic University of Norway, has also recently joined the team as Assistant Editor. This issue features contributions on ritual performance, visual repatriation, agricultural imaginaries, linguistic justice, and archival critique, exemplifying the journal’s evolving commitment to multimodal, interdisciplinary, and regionally grounded scholarship.